Can Reminders Promote Regular Pro-Environmental Behavior? Experimental Evidence from Peru - Hanna Fuhrmann-Riebel; Ben D'Exelle; Kristian López Vargas; Sebastian Tonke; Arjan Verschoor (Institute of Labor Economics (IZA), 2024)
Tackling environmental pollution requires a permanent change in regular, repeated behavior of households. Bringing about change in such behavior may require interventions that are not limited to a single point in time, yet little evidence exists on how frequently we need to target households to initiate behavioral change and to form new habits in regular pro-environmental behavior. To fill this gap, we investigate the impact of mobile text reminders on households' recycling behavior in urban Peru, by randomly varying the frequency of reminders over a nine-week treatment period. We find that reminders increase both the likelihood that households start to recycle, and the frequency of recycling among households that already recycled before the intervention. The effects are stronger if reminders are repeated over a longer period. Our findings suggest that low-cost mobile text reminders can support repeated pro-environmental behavior, and that some repetition may be needed to maximize their effectiveness.
Keywords: C93; D83; D90; D91; Q53; Q58; 330; recycling; habit formation; limited attention; reminders; Peru